State-of-the-Art Treatment and Novel Agents in Local and Distant Recurrences of Cervical Cancer - Tempfer, Clemens B.; Beckmann, Matthias (Oncology Research and Treatment, 2016)
Depending on the stage at initial presentation, cervical cancer will recur in 25-61% of women. Typical manifestations of recurrent cervical cancer include the central pelvis and the pelvic side walls as well as retroperitoneal lymph node basins in the pelvis and the para-aortic region, and - more rarely - supraclavicular lymph nodes. There are no typical symptoms of recurrent cervical cancer. Women with suspected recurrence after cervical cancer based on gynecological examination or organ-specific symptoms must undergo imaging studies and - if technically feasible - biopsy with histological verification, especially in cases of distant metastases, in order to rule out a second primary. Radiotherapy-naïve women should be treated with salvage radiochemotherapy with curative intention. For women with previous radiotherapy, surgery in the form of hysterectomy, local resection, or pelvic exenteration is the treatment of choice. Pelvic exenteration can lead to cure in selected patients, but at the price of a high rate of complications and significant morbidity and mortality. If complete surgical resection is not feasible or if the woman is not a candidate for surgery, chemotherapy with palliative intent should be offered. Patients with recurrent disease outside the pelvis are candidates for systemic chemotherapy. Several agents have shown to be active in this situation, either in single-agent or combination regimens. Platinum-containing regimens have a superior efficacy over non-platinum regimens and bevacizumab may be added to chemotherapy.
EVALuna2:32962